EVALUATION OF WORK-LIFE BALANCE, DEPRESSION, AND JOB PERFORMANCE IN RESIDENT DOCTORS - Istiqomah, Ratri; Putra, Kuswantoro Rusca (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2025)
Introduction: Mental health and work performance of resident doctors are critical, given the high workload and challenges in balancing professional duties with personal life. This study evaluates the condition of work-life balance (WLB), depression, and job performance among resident doctors in one of teaching hospital in Indonesia. This study aims to evaluate the impact of a mindfulness training program on WLB, depression, and job performance of resident doctors and assess the changes in these variables before and after the program. Methods: A total of 314 resident doctors were initially assessed, and 99 doctors with mild to severe depression were selected for the intervention. Of these, 70 doctors participated in a training program consisting of three sessions: effective communication, mindfulness, and patient safety. Pre-test and post-test assessments were conducted using the PHQ-9 for depression, IWPQ for job performance, and a work-life balance scale. Results: Before the intervention, most doctors reported low WLB (51.4%) and mild depression (72.9%). Job performance was predominantly rated as moderate (81.4%). After the intervention, there was a significant reduction in depression levels, with 38.6% of doctors reporting normal depression levels, 42.9% reporting mild depression, and 8.6% reporting severe depression. The p-value for depression was 0.000, indicating a significant improvement in the mental health of the doctors. However, the results for WLB did not show significant improvement (p = 0.303), and job performance also did not show significant improvement (p = 0.162) after the intervention. Despite a slight increase in the number of doctors reporting high job performance after the intervention (from 7.1% pre-intervention to 11.4% post-intervention), the change was not statistically significant. Discuss: The results of this study indicate that the training program significantly reduced depression among resident doctors, no significant improvements were observed in WLB or job performance. Despite the intervention’s focus on improving mental health, the findings suggest that external factors, such as workload and organizational support, may play a more significant role in influencing WLB and job performance. These results underscore the complexity of improving job performance and WLB, highlighting the need for a more holistic approach that combines mental health interventions with systemic changes in the work environment. Future studies should explore longer, more comprehensive interventions and address the structural factors affecting healthcare professionals’ WLB and job performance. Conclusion: The mindfulness and communication training intervention was effective in significantly reducing depression among resident doctors but did not significantly affect WLB or job performance. Further studies with different interventions may be required to achieve broader improvements in WLB and job performance.